Requirements for the accuracy of the existing and newly built planned geodesic networks in the area - Madumarov Bahromjon Bahodirjon ogli; Mirzaakhmedov Sayyodjon Shukhratjon ogli (Zien Journals, 2023)
This article covers in detail the requirements for them when building state geodesic nets. Concepts are also given about the accuracy and mechanism of operation of the height networks of State geodesic networks.
Keywords: state geodesic lattice; map; triangulation polygonometry trilateration plan